Revisiting anesthesia-induced preconditioning for neuroprotection in the aging brain: a narrative review - Tao Zhang; Woosuk Chung; Beverley A. Orser (Korean Journal of Anesthesiology, 2025)
The growing number of older adults undergoing surgery necessitates that we address the adverse effects of overt and covert perioperative stroke. Preclinical studies have suggested that anesthesia-induced preconditioning may provide neuroprotection by preserving mitochondrial function, activating cytosolic signaling pathways, and reducing neuroinflammation. However, these promising findings from animal studies have not yet translated into improved clinical outcomes. The discordance between preclinical and clinical outcomes may be due to age-related mitochondrial dysfunction and other comorbidities in older human populations, which reduce the effectiveness of anesthetic preconditioning. Mitochondria, which are central to the effectiveness of preconditioning, may be therapeutic targets to restore the neuroprotective effects of anesthetic preconditioning in the aging brain. Emerging evidence suggests that physical prehabilitation, a key component of Enhanced Recovery After Surgery programs, may influence mitochondrial function and could thus, restore anesthesia-induced preconditioning. Although further research is needed to determine the impact of physical prehabilitation on mitochondrial function and anesthetic preconditioning, incorporating physical prehabilitation into perioperative care might enhance neurological outcomes for older patients undergoing surgery.